A highly differentiated region of wheat chromosome 7AL encodes a Pm1a immune receptor that recognizes its corresponding AvrPm1a effector from Blumeria graminis. Issue 5 (15th December 2020) - Hewitt, Tim; Müller, Marion C.; Molnár, István; Mascher, Martin; Holušová, Kateřina; Šimková, Hana; Kunz, Lukas; Zhang, Jianping; Li, Jianbo; Bhatt, Dhara; Sharma, Raghvendra; Schudel, Seraina; et al.
Summary: Pm1a, the first powdery mildew resistance gene described in wheat, is part of a complex resistance (R) gene cluster located in a distal region of chromosome 7AL that has suppressed genetic recombination. A nucleotide‐binding, leucine‐rich repeat (NLR) immune receptor gene was isolated using mutagenesis and R gene enrichment sequencing (MutRenSeq). Stable transformation confirmed Pm1a identity which induced a strong resistance phenotype in transgenic plants upon challenge with avirulent Blumeria graminis (wheat powdery mildew) pathogens. A high‐density genetic map of a B .  graminis family segregating for Pm1a avirulence combined with pathogen genome resequencing and RNA sequencing (RNAseq) identified AvrPm1a effector gene candidates. In planta expression identified an effector, with an N terminal Y/FxC motif, that induced a strong hypersensitive response when co‐expressed with Pm1a in Nicotiana benthamiana . Single chromosome enrichment sequencing (ChromSeq) and assembly of chromosome 7A suggested that suppressed recombination around the Pm1a region was due to a rearrangement involving chromosomes 7A, 7B and 7D. The cloning of Pm1a and its identification in a highly rearranged region of chromosome 7A provides insight into the role of chromosomal rearrangements in the evolution of this complex resistance cluster.